ICHTHYOFAUNAL DIVERSITY AND CPUE (Catch per unit effort) UNAL DIVERSITY AND CPUE (Catch per unit effort) AT WATLAB GHAT, WULAR LAKE, KASHMIR - AND M. H. BALKHI2, SYED TALIA MUSHTAQ , SYED AALIA MUSHTAQ (The Bioscan, 2018)
The present work was aimed at having a detailed account of the fish diversity and Catch Per Unit Effort of Watlab Ghat (a major fish landing centre) in Wular Lake. In a one year study period, nine species of freshwater fishes,both native and exotic belonging to two orders were recorded. Cyprinidae was observed to be the most dominant family. The minimum and maximum CPUE was recorded as 115 g/man-hour in the month of November and 2827.5 g/man-hour in the month of June respectively. As far as the diversity is concerned, the highest Shannon’s diversity index was obtained as 1.74 in the month of December while as lowest was recorded as 1.07 in the month of February. Likewise, the highest and lowest Pielou’s evenness indices were recorded as 0.75 and 1 in the months of August and November respectively. The highest values for Simpson’s Dominance indices were recorded in the months of December and April as 0.82 and 0.65 respectively. The study revealed that there was a drastic decline in the native Schizothorax due to the introduction of exotic common carp, pollution and other anthropogenic disturbances.